Web-Based E-Learning Application to Support the Teaching and Learning Process at Genta Syaputra Senior High School - Euis Nurninawati; Ruli Supriati; Alpi Maulana (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2023)
Along with the rapid development of technology today, we need a tool or method that can take advantage of existing technology in order to support the teaching and learning process at an educational institution, making it easier for students to understand the teaching and learning process using online methods in this COVID-19 era. The purpose of this study was to find out how the use of e-learning as a learning medium and the factors that influence it in SMA Genta Syaputra Regency were studied based on the characteristics of e-learning consisting of Non-linearity, Self-managing, Feedback-interactivity, Multimedia-Learners style, Just in Time, Dynamic Updating, Easy Accessibility and Collaborative Learning. This study uses a descriptive design using observation, interviews, and literature study. System analysis method using UML,analysis database using ERD and prototype design using Mockup. The results of this study concluded that the condition of the use of e-learning as a learning medium in SMA Genta Syaputra Regency is in a fairly good condition with a percentage level of 78%.